Reflections on Peter Nagel's article : "Problematising the Divinity of Jesus: Why Jesus is not Theos" - including a short history of the doctrine of the Trinity - Jones, Christopher D. (2024)
This is a response to an article written by South African New Testament scholar, Peter Nagel. The article draws on the thoughts of another South African New Testament scholar Andries van Aarde and of German theologian Bernhard Lohse, on the history of the doctrine of the Trinity. Concluding observations include inquiring as to how the church will effectively address this type of study in its deliberations and decisions.
Keywords: Athanasius; Augustine; Divinity; Doctrine; Iesous; Irenaeus; Lohse; Nagel; Nicaea; Origen; Theos; Trinity; Van Aarde; Divinity; Doctrine